Hepatic vein thrombosis secondary to COVID-19 - Kushal Markanday; Nitin Bhardwaj; Buvana Radhakrishnan; P Gopinath Kumar (Wolters Kluwer Medknow Publications, 2021)
COVID-19 is known to cause both arterial and venous thromboembolism. Although a lot of attention is being given to those presenting with myocardial infarction and stroke, splanchnic vein thrombosis which includes portal, mesenteric, splenic, and hepatic vein thrombosis is often underreported. A 21-year-old female presented with progressive abdominal distension and obstipation for the past 2 weeks. The patient was diagnosed as a case of moderate COVID-19 illness 2 weeks before the onset of these symptoms and recovered on receiving treatment according to the COVID protocol. Physical examination revealed pallor and bilateral pitting pedal edema up to ankles. Systemic examination revealed uniformly distended abdomen with signs of free fluid and tenderness in the right hypochondrium. Hematological investigations showed moderate-grade microcytic hypochromic anemia. Biochemically, indirect hyperbilirubinemia and transaminitis with moderately elevated D-dimers and Lactate dehydrogenase (LDH) was noted. Radiological imaging of the abdomen (including USG with doppler and CT contrast Scans) revealed gross ascites, nutmeg appearance of liver with completely obscured hepatic veins indicating no flow of blood, multiple intrahepatic portosystemic collaterals and a partially thrombosed inferior vena cava with no evidence of portal hypertension. All other workup to rule out other causes of hepatic vein thrombosis was inconclusive. The patient was treated with low-molecular-weight heparin and then continued with oral warfarin at discharge. On a 4-week follow-up, the patient showed marked clinical improvement with partial resolution of presenting symptoms.